DPs, Phi-features and Tense in the Context of Abyssinian (Eritrean and Ethiopian) Semitic Languages A Window for Further Research - Tewolde, Tesfay (Biblioteca di Studi di Filologia Moderna, 2016)
This study discusses DPs, Phi-features and Tense in Abyssinian Semitic languages. DPs and TPs have parallel structures. Their subjects are generated within the projection of lexical categories which move to Spec positions of associated non-lexical categories (Fukui 2006). Aspect is indicated by inserting different vowel patterns into the roots of base stems. Tense, however, is indicated by different forms of verb to be (Jelinek 2002). In North Abyssinian Semitic languages, verbs and nouns have similar patterns to indicate plurality and this is due to an economy constraint on the grammar (Siddiqi 2009). Phi-features in the affixes and independent pronouns are closely related (Buccellati 1996). We may assume the development of the latter into the former or vice versa via a clitic stage (Fuß 2005).